Substantiation of the content of petroleum products in soil (soils) of variouspurposes - Stankevych, V.V.; Koval, N.M. (Environment & Health, 2018)
Objective : We substantiated the hygienic standard of the content of petroleum products (total) in agricultural soils and soils of the settlements’ territories of various functional use. Materials and methods : We used the gravimetric method for the determination of the actual content of totalpetroleum products in the samples of soils of the agricultural lands and soils from the territories of the settlements of various functional purposes. Under experimental conditions, we investigated the influence of different concentrations of petroleum products on the enzymatic (dehydrogenase) activity of soil microorganisms on the model soil media with different content of humus. Results: Soils with a higher content of humus are more resistant to the impact of oil products. Concentrations of the gasoline-diesel fraction of PP from 1.0 to 5.0 g/kg had a stimulating effect on the enzymatic activity of soil microflora and on the development of the crops for all types of soils; concentrations over 10.0 up to 20.0 g/kg inhibited this parameter sharply. The petrol fraction of PP provided more toxic effect on this indicator in comparison with the diesel fraction. When assessing the territories of different planning zones of the settlements, the significant fluctuations in the concentrations of the petroleum products were established, but with a certain correlation, depending on thef unctional zone. A streetroad dust is especially instructive by the artificial soils’ pollution levels. Conclusions.The allowable levels of oil products’ pollution were proposed for different planning zones of the territories of the settlements. As a safe concentration for the sum of petroleum products at the level of 1.0 g / kg (1000.0 mg / kg of soil) is proposed for the soils of agricultural purpose.